Discomfort: a new material for interaction design - schraefel, m. c.; Jones, Michael (Frontiers in Computer Science, 2023)
We present discomfort as a new material for HCI researchers and designers to consider in applications that help a person develop a new skill, practice or state. In this context, discomfort is a fundamental precursor of adaptation and adaptation leads to new skill, practice or state. Engaging effectively with discomfort may lead to increased personal development. The way in which discomfort is perceived, and when it is experienced, is often part of a rationale for rejecting or adopting a practice. Factors that influence the choice to accept or reject a practice of discomfort create opportunities for interaction design that facilities discomfort. We propose incorporating discomfort-as-material into our designs explicitly as a mechanism to make desired adaptations available to more of us, more effectively and more of the time. To explore this possibility, we offer an overview of the physiology and neurology of discomfort in adaptation and propose 3 issues related to incorporating discomfort into design: preparation for discomfort, need for recovery, and value of the practice.